The impact of coping strategies on parental death among young people - Zulian Fikry (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Parental death has a diverse impact on children. Losing is a situation that brings challenges to person who had left behind. The death of parents obscures the figure of a parent who has an important meaning for the development of a child. The result of the loss of a parent figure in the family can cause a variety of negative impacts on the child who is left behind. This qualitative research aims to investigate the ability of stress coping strategies in dealing with the death of parents. Parental death causes a severe psychological burden because the source of love and guidance causes feelings of loneliness, despair, and fear. The feeling of stress has a negative impact on mental health if it is not overcome by a stress coping strategy. This research data was collected using in-depth interviews with teenager who lost their parents in the city of Yogyakarta Indonesia. The results of this study found that death did trigger stress that had never been felt before is the emergence of a deep sadness, anxiety about the fate of self and family in the future, changes in individual attitudes and characters, the emergence of insights about the process of maturity, trying to limit themselves from the relationship, feeling of being unable to economically supported, and a great longing for the figure of parents who died